Hospitalization rates of children who are blind. (11th April 2013) - Crewe, Julie M; Lam, Geoff; Clark, Antony; Spilsbury, Katrina; Mukhtar, Aqif S; Morlet, Nigel; Morgan, William H; Crowley, Margaret; Semmens, James B
Abstract: Background: To evaluate the impact of blindness on hospitalization rates of children. Design: Matched cohort study. Participants: Children confirmed as legally blind (2003–2009), age‐ and gender‐matched to control cohort of normally sighted children from the state register of births. Methods: The rates and reasons for admission to hospital were compared using hospital morbidity records. The association of blindness with rates of admission and length of stay in hospital, 2003–2010, were estimated using multivariate negative binomial regression models. Main Outcome Measures: Descriptive statistics, incident rate ratios, and predicted means for hospital separations and length of stay. Results: Fifty‐nine blind and 59 control children had a combined total of 107 separations accounting for 237 bed days in hospital after the index date of legal blindness. The median age at the index date was 8 years. Over 90% of separations and 92% of bed days were incurred by 22 blind children. Blind children had four (95% confidence interval 1.9–9.3) times more hospital separations and stayed in hospital six (95% confidence interval 1.9–17.5) times longer than the control cohort children. There were more than 40 times as many comorbidities recorded by the blind children ( n  = 201) compared with the control children ( n  = 5). A third of the blind children were hospitalized for respiratory conditions. Conclusions: Children who are born or become blind in childhood have more and longer periods in hospital than sighted children likely because of complex comorbid health problems. There was a disproportionate incidence of comorbid respiratory diseases in the blind children.